Migrant identity constructs: identities in resistance and strategic identities in Haitian children in Santiago de Chile - Ibáñez, Karen (2020)
In recent years, the arrival of the Haitian population in Chile has been increasing and has been characterized by a complex process of social insertion, which has had repercussions in the field of education. In this regard, this study is situated in the field of cultural conflict by seeking to interpret the identity constructions experienced by children from Haiti on the basis of social practices and perceptions of the socio-educational environment in a school in Santiago de Chile, from the conceptualization of difference and intersectionality in migration. In this way, it is realized that children from Haiti build their identities from identities in resistance and strategic identities. To account for this, the research is based on the thesis of the degree in anthropology. A qualitative methodological strategy was developed through school ethnography with a year-long field work, in which participant observation and in-depth interviews were conducted. The aim was to highlight a critical stance with respect to the importance of rescuing the perspective of children and their capacity for agency.